On the Security Of A Certificateless Signcryption With Known Session-Specific Temporary Information Security In The Standard Model. (10th January 2020) - Lin, Xi-Jun; Sun, Lin; Yan, Zhen; Zhang, Xiaoshuai; Qu, Haipeng
Abstract: Rastegari et al . recently proposed a certificateless signcryption (CL-SC) scheme. They claimed that their scheme is the first secure CL-SC scheme, which captures the known session-specific temporary information security (KSSTIS), in the standard model. In this paper, we point out that their scheme is insecure, which implies that how to construct a secure CL-SC scheme with KSSTIS in the standard model is still an open problem.